Pre and protohistoric stone architectures, Volume 1, Session XXXII-3 comparisons of the social and technical contexts associated to their building : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France) - Cousseau, Florian; Laporte, Luc 1962- (Archaeopress Archaeology, 2020)
Proceedings, with full text in English and French, from session XXXII-3 of the XVIII UISPP World Congress, Paris, 2018. The volume aims to break the usual limits on the fields of study and to deconstruct some preconceived ideas
"Available both in print and Open Access"--Homepage. - Conference proceedings. - Also issued in print: 2020. - Includes bibliographical references
Keywords: Vor- und Frühgeschichte; Architecture, Ancient / Europe / Congresses; Building, Stone / Europe / Congresses; Excavations (Archaeology) / Europe / Congresses; Steinbau; Konferenzschrift -- 2018 -- Paris